Linking functional composition moments of the sub-Mediterranean ecotone with environmental drivers - de Tomás Marín, Sergio; Galán Díaz, Javier; Rodríguez-Calcerrada, Jesús; Prieto, Iván; de la Riva, Enrique G. (Frontiers in Plant Science, 2023)
Introduction: Functional trait-based approaches are extensively applied to the study of mechanisms governing community assembly along environmental gradients. These approaches have been classically based on studying differences in mean values among species, but there is increasing recognition that alternative metrics of trait distributions should be considered to decipher the mechanisms determining community assembly and species coexistence. Under this framework, the main aim of this study is to unravel the effects of environmental conditions as drivers of plant community assembly in sub-Mediterranean ecotones. Methods: We set 60 plots in six plant communities of a sub-Mediterranean forest in Central Spain, and measured key above-and belowground functional traits in 411 individuals belonging to 19 species, along with abiotic variables. We calculated community-weighted mean (CWM), skewness (CWS) and kurtosis (CWK) of three plant dimensions, and used maximum likelihood techniques to analyse how variation in these functional community traits was driven by abiotic factors. Additionally, we estimated the relative contribution of intraspecific trait variability and species turnover to variation in CWM.The first three axes of variation of the principal component analyses were related to three main plant ecological dimensions: Leaf Economics Spectrum, Root Economics Spectrum and plant hydraulic architecture, respectively. Type of community was the most important factor determining differences in the functional structure among communities, as compared to the role of abiotic variables. We found strong differences among communities in their CWMs in line with their biogeographic origin (Eurosiberian vs Mediterranean), while differences in CWS and CWK indicate different trends in the functional structure among communities and the coexistence of different functional strategies, respectively. Moreover, changes in functional composition were primarily due to intraspecific variability. Conclusions: We observed a high number of strategies in the forest with the different communities spreading along the acquisitive-conservative axis of resource-use, partly matching their Eurosiberian-Mediterranean nature, respectively. Intraspecific trait variability, rather than species turnover, stood as the most relevant factor when analyzing functional changes and assembly patterns among communities. Altogether, our data support the notion that ecotones are ecosystems where relatively minor environmental shifts may result in changes in plant and functional composition.